Suppression of Methane Generation during Methanogenesis by Chemically Modified Humic Compounds - Elena Efremenko; Olga Senko; Nikolay Stepanov; Nikita Mareev; Alexander Volikov; Irina Perminova (MDPI AG, 2020)
The introduction of various concentrations of chemically modified humic compounds (HC) with different redox characteristics into the media with free and immobilized anaerobic consortia accumulating landfill gases was studied as approach to their functioning management. For this purpose, quinone (hydroquinone, naphthoquinone or methylhydroquinone) derivatives of HC were synthesized, which made it possible to vary the redox and antioxidant properties of HC as terminal electron acceptors in methanogenic systems. The highest acceptor properties were obtained with potassium humate modified by naphthoquinone. To control possible negative effect of HC on the cells of natural methanogenic consortia, different bioluminescent analytical methods were used. The addition of HC derivatives, enriched with quinonones, to nutrient media at concentrations above 1 g/L decreased the energetic status of cells and the efficiency of the methanogenesis. For the first time, the significant decrease in accumulation of biogas was reached as effect of synthetic HC derivatives, whereas both notable change of biogas composition towards increase in the CO2 content and decrease in CH4 were revealed. Thus, modification with quinones makes it possible to obtain low-potential HC derivatives with strongly pronounced acceptor properties, promising for inhibition of biogas synthesis by methanogenic communities.